Regional unemployment, gender and time allocation of the unemployed - Jose Ignacio Gimenez-Nadal; José Alberto Molina (Institute for the Study of Labor (IZA), 2012)
This paper analyzes the relationship between time allocation decisions of the unemployed, gender, and regional unemployment rates. Using the Spanish Time Use Survey 2002-2003 and 2009-2010, we find that higher regional unemployment rates are associated with increases in the time devoted to study by men, and to household production by women, and with decreases in the time devoted to personal care by men and leisure by women. We also find evidence favoring consumption smoothing as the channel through which others' unemployment affects time allocation decisions of the unemployed. As higher regional unemployment rates imply a lower availability of jobs for the unemployed, it decreases the expectations individuals have of finding a job, and thus households may try to increase their time spent on household production to reduce the market expenditures needed to maintain their consumption. We interpret our results as evidence that others' unemployment has several effects that need to be considered in the analysis of the wellbeing of the unemployed during business cycles.
Keywords: D13; J16; J22; 330; unemployment; time use; regional unemployment rates; gender; Arbeitslosigkeit; Zeitverwendung; Geschlecht; Hausarbeit; Regionale Arbeitslosigkeit; Spanien